2014
DOI: 10.7314/apjcp.2014.15.22.9557
|View full text |Cite
|
Sign up to set email alerts
|

MiRNA Molecular Profiles in Human Medical Conditions: Connecting Lung Cancer and Lung Development Phenomena

Abstract: MiRNAs are endogenous, single stranded ~22-nucleotide non-coding RNAs (ncRNAs) which are transcribed by RNA polymerase II and mediate negative post-transcriptional gene regulation through binding to 3'untranslated regions (UTR), possibly open reading frames (ORFs) or 5'UTRs of target mRNAs. MiRNAs are involved in the normal physiology of eukaryotic cells, so dysregulation may be associated with diseases like cancer, and neurodegenerative, heart and other disorders. Among all cancers, lung cancer, with high inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 100 publications
0
15
0
Order By: Relevance
“…These molecules have diverse biological functions in glioma initiation and progression [4–8]. More than half of all miRNAs inhibit target gene expression by binding to complementary sequences in the 3’ untranslated regions of mRNAs [9, 10]. A single miRNA may have hundreds of mRNA targets, and a single gene may have hundreds of miRNA regulators.…”
Section: Introductionmentioning
confidence: 99%
“…These molecules have diverse biological functions in glioma initiation and progression [4–8]. More than half of all miRNAs inhibit target gene expression by binding to complementary sequences in the 3’ untranslated regions of mRNAs [9, 10]. A single miRNA may have hundreds of mRNA targets, and a single gene may have hundreds of miRNA regulators.…”
Section: Introductionmentioning
confidence: 99%
“…Of the predicted top 50 lung neoplasm-related miRNAs, all were found in the above three databases. However, Aghanoori et al 92 found that hsa-mir-302d was down-regulated in lung cancer tissue. Therefore, supporting evidence for the prediction capabilities of LSGSP for potential disease-miRNA associations and isolated disease-miRNA associations was found from the databases and was validated by the latest literature studies, which means that LSGSP has excellent predictive performance.…”
Section: Isolated Disease-related Mirna Predictionmentioning
confidence: 98%
“…Through interactions with a negative regulatory sequence in the 3'-non-coding region of specific mRNA targets, miRNA regulation is involved in a wide variety of normal and abnormal cell behaviors (10). miRNAs have potential as tumor biomarkers (11). Although the functions of a number of miRNAs have yet to be elucidated, miRNAs have been implicated in a wide range of physiological and developmental processes (10).…”
Section: Introductionmentioning
confidence: 99%